2012
DOI: 10.1097/gme.0b013e318223e6b3
|View full text |Cite
|
Sign up to set email alerts
|

Walking training in postmenopause

Abstract: In postmenopause, participation in a program of aerobic physical exercise can result in a reduction of spontaneous physical activity, which inhibits the positive effects of the aerobic exercise on plasma lipids and lipoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…The variability in behavior across groups and even within the EX group highlights the need for objective monitoring of physical activity and sedentary behavior during any interventions examining the effects of exercise or sedentary time. It also supports the work of Di Blasio et al (2012), who suggested some individuals may require additional intervention when beginning an exercise training program to ensure behavioral compensation does not occur. Taken together, the observed variability in response to the intervention and the known variability in metabolic response to exercise training support the notion that a larger sample is needed to detect between-group differences.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The variability in behavior across groups and even within the EX group highlights the need for objective monitoring of physical activity and sedentary behavior during any interventions examining the effects of exercise or sedentary time. It also supports the work of Di Blasio et al (2012), who suggested some individuals may require additional intervention when beginning an exercise training program to ensure behavioral compensation does not occur. Taken together, the observed variability in response to the intervention and the known variability in metabolic response to exercise training support the notion that a larger sample is needed to detect between-group differences.…”
Section: Discussionsupporting
confidence: 65%
“…However, when individuals begin exercise training they may compensate by decreasing their physical activity throughout the rest of the day, including activities of daily living, maintaining posture, and ambulation (Garland et al 2010; King et al 2007; Levine et al 2000; Melanson et al 2013). If compensation occurs, the magnitude of weight loss and improvements in health following exercise training may be attenuated (Di Blasio et al 2012; Manthou et al 2009). As non-exercise physical activity decreases, there is an increase in time spent in sedentary behaviors (awake, sitting/lying with low levels of EE (<1.5 METs)) (Garland et al 2010; King et al 2007; Levine et al 2000; Melanson et al 2013; Sedentary Behavior Research Network, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies where NEEx has been estimated using other less precise techniques, including accelerometry (16), a combination of accelerometry and heart rate monitoring (35), heart rate monitoring with individual heart rate energy expenditure calibration (17, 21, 31) or SenseWear Pro arm band (5) have shown no change in NEEx in response to aerobic exercise training. However, Morio et al .…”
Section: Discussionmentioning
confidence: 99%
“…A number of short term (2 to 14 days) (2, 1921, 31, 32, 36, 40), non-randomized (4, 5, 13, 17, 2224, 26) and randomized trials (3, 12, 16, 28, 29, 35) have evaluated the effect of exercise training on NEEx or non-exercise physical activity (NEPA) with mixed results. Irrespective of study design (i.e., short-term cross-over, non-randomized, randomized trials) the majority of studies do not observe reductions in reported NEPA (3, 19, 20, 29, 36) or NEEx (5, 12, 16, 17, 21, 24, 28, 31, 32, 35, 40) in response to prescribed aerobic exercise. Studies that reported decreased NEEx (4, 13, 26) or NEPA (22, 23) in response to prescribed exercise utilized non-randomized designs and were generally conducted in small samples (≤15/group) of overweight or obese older adults (i.e., >55 years).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this review suggested that there is conflicting evidence as to the existence of an activitystat with 63, 40 and 80 % of studies involving children, adult and older adult studies respectively, reporting evidence of compensation in either physical activity or energy expenditure [11]. Several experimental papers investigating compensation have been published since this review [1221], and similarly report conflicting results. In children and adults, several recent studies have shown some evidence of compensation with an imposed exercise stimulus [1215], however there are at least as many that demonstrate no evidence of an activitystat or compensatory effect [1619].…”
Section: Introductionmentioning
confidence: 99%